The Influence of Project-Based Learning on Students' Critical Thinking in Social Studies - Siti Romlah; Siti Winis Sudani (Yayasan Cerdas Pedia Indonesia, 2025)
The Indonesian educational landscape is undergoing a critical transition toward competency-based frameworks under the Kurikulum Merdeka to address systemic gaps in students' higher-order thinking skills. This study examines the influence of Project-Based Learning (PjBL) on critical thinking within Social Studies education. Utilizing a systematic meta-synthesis of empirical evidence from 2021–2025, the research explores how PjBL triggers cognitive indicators defined by Facione and Ennis. Findings indicate that PjBL significantly enhances analytical and evaluative depth, achieving high Normalized Gain scores. Furthermore, the integration of digital tools like Canva and TikTok, synthesized with Ki Hajar Dewantara’s Among System, fosters both modern digital literacy and localized cultural autonomy. Despite its effectiveness, systemic barriers such as teacher readiness and the digital divide persist. The study concludes that sustainable PjBL implementation requires continuous professional development and infrastructure equity to successfully transform passive learning into active, inquiry-based investigation, ultimately fulfilling the objectives of the Pancasila Student Profile.